2018
DOI: 10.1093/jas/sky074
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of post-ACTH challenge salivary cortisol concentrations for identifying horses with equine glandular gastric disease1

Abstract: The aims of this study were to better characterize the adrenal response to i.v. adrenocorticotropic hormone (ACTH) in horses with and without gastric disease and to validate and simplify the ACTH stimulation test by determining the diagnostic accuracy of six consecutive sampling time points after ACTH administration for equine glandular gastric disease (EGGD) and equine squamous gastric disease (ESGD). Twenty-six endurance and eventing horses without clinical disease [Sport Horse Population (SHP)] and an indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…Notably, 60 minutes post-stimulation appeared to be the most informative time point, as linear regression models evaluating cortisol concentrations after 90 minutes showed no significant outcome. This is in agreement with our previous study [43], where sampling after 60 minutes also revealed the best association with the occurrence of glandular gastric disease. The present study supports our previous hypothesis [43] that predominantly the initial increase of cortisol after ACTH stimulation is important for the evaluation of the cortisol responsiveness in the context of stress-related disorders.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Notably, 60 minutes post-stimulation appeared to be the most informative time point, as linear regression models evaluating cortisol concentrations after 90 minutes showed no significant outcome. This is in agreement with our previous study [43], where sampling after 60 minutes also revealed the best association with the occurrence of glandular gastric disease. The present study supports our previous hypothesis [43] that predominantly the initial increase of cortisol after ACTH stimulation is important for the evaluation of the cortisol responsiveness in the context of stress-related disorders.…”
Section: Discussionsupporting
confidence: 94%
“…For the ACTH stimulation test, based on the estimated weight, a dose of 1 μg/kg BW synthetic ACTH1-24 (Synacthen tetracosactidum 0.25 mg/ml equivalent to 25 IU/mL; Novartis, Vilvoorde, Belgium) was injected intravenously. The dosage was chosen based on previous publications [19, 20, 39, 40]. Saliva samples were taken with salivettes (Sarstedt, Nuembrecht, Germany) before (0 minute – baseline; T0) and 60 (T60) and 90 (T90) minutes after ACTH administration.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, due to the nonspecific clinical signs associated with EGUS, diagnosis based on clinical signs is unreliable. Blood sucrose and salivary cortisol response to adrenocorticotropin (ACTH) have been evaluated for their diagnostic usefulness in EGGD, but both tests were unreliable 2,3. Endoscopic examination enabling visualization of the lesions in the stomach is the only method to achieve a definitive diagnosis.…”
Section: Diagnosismentioning
confidence: 99%